Pengaruh Konten TikTok dan Influencer Marketing terhadap Keputusan Pembelian dengan Pendapatan sebagai Variabel Kontrol - Didi Andri; Ahmad Fadli; Eko Pratandi; Muhammad Tareq Hanafi Majid (Faculty of Economics and Business University of Mataram, 2026)
This research is conducted to examine how influencer marketing and TikTok content impact the purchasing decisions of Generation Z in the Mataram City area, with income level as a controlled variable. The method applied is a quantitative approach of the causal associative type. The determination of the sample was conducted using purposive sampling techniques, involving 85 individuals from Generation Z in the city of Mataram who are active users of the TikTok application and have been exposed to promotions from influencer figures. Field data collection was conducted using a Likert scale questionnaire, which was then processed using multiple linear regression analysis with the aid of SPSS version 25 software. The research findings indicate the absence of a significant influence of the TikTok content variable on purchasing decisions, as shown by the significance value of 0.740 > 0.05. On the other hand, influencer marketing has a positive and significant impact on consumer decisions, as evidenced by a significance value of 0.001 < 0.05. Meanwhile, income, positioned as a control variable, proved to be the most dominant factor and had a significant influence on the decision to purchase, with a significance level of 0.000 < 0.05. Simultaneous testing shows that the combination of income, influencer marketing, and TikTok content has a significant impact on the decision-making process with a significance value of 0.000 < 0.05. Furthermore, the acquisition of an Adjusted R Square value of 0.903 means that 90.3% of the variation in purchasing decisions can be explained by the research model used.